First-in-Human Phase I Study of Envafolimab, a Novel Subcutaneous Single-Domain Anti-PD-L1 Antibody, in Patients with Advanced Solid Tumors. (27th May 2021) - Papadopoulos, Kyriakos P.; Harb, Wael; Peer, Cody J.; Hua, Qiong; Xu, Siying; Lu, Haolan; Lu, Ni; He, Yue; Xu, Ting; Dong, Ruiping; Gong, John; Liu, David
Abstract : Lessons Learned : Subcutaneous injection was an effective route of administration for envafolimab with a favorable pharmacokinetic profile in patients with previously treated advanced solid tumors. Subcutaneous envafolimab was well tolerated and had durable antitumor activity at a wide range of doses and schedules. Envafolimab has the potential to be a more convenient option than currently approved intravenous PD-1/PD-L1 inhibitors. Background: Envafolimab is a novel fusion of a humanized single-domain PD-L1 antibody and human IgG1 Fc fragment formulated for subcutaneous injection. This study explored the safety and feasibility of subcutaneous administration of envafolimab as an alternative to intravenous administration of PD-1/PD-L1 inhibitors in the treatment of advanced, refractory solid tumors. Methods: This was a first-in-human, open-label phase I trial. In a dose-escalation phase, patients received subcutaneous envafolimab 0.01–10 mg/kg once weekly following a modified 3+3 design. In a dose-exploration phase, patients received subcutaneous envafolimab 300 mg once every 4 weeks. Results : Twenty-eight patients were enrolled (dose escalation n = 18, dose exploration n = 10, median age 66 years; 71% male; ECOG performance score = 0 [21%] or 1 [79%]). No dose-limiting toxicities or injection-site reactions were reported. Envafolimab demonstrated dose-proportional increases in area under the time-concentration curve and maximum plasma concentration. Median time to maximum plasma concentration was 4–7 days. In the dose-exploration phase, terminal half-life was 14 days after dose 1 in cycle 1 and 23 days at steady state. Three patients experienced a confirmed partial response. Conclusion : Subcutaneous envafolimab had a favorable safety and pharmacokinetic profile, with promising preliminary antitumor activity in patients with advanced solid tumors.